(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author reveals some aspects of sentencing under aggravating circumstances, provides the concept of aggravating circumstances, as well as analyzes their list. The author deals with the operation of the courts when sentencing under aggravating circumstances. The author also proposes to amend the current legislation of the Republic of Kazakhstan. Key words: Sentencing, aggravating circumstances, a criminal offense, objective and subjective symptoms, identity of the guilty.